Partial Support for an Interaction Between a Polygenic Risk Score for Major Depressive Disorder and Prenatal Maternal Depressive Symptoms on Infant Right Amygdalar Volumes - Acosta H; Kantojärvi K; Hashempour N; Pelto J; Scheinin NM; Lehtola SJ; Lewis JD; Fonov VS; Collins DL; Evans A; Parkkola R; Lähdesmäki T; et al. (United Kingdom, 2022)
Psychiatric disease susceptibility partly originates prenatally and is shaped by an interplay of genetic and environmental risk factors. A recent study has provided preliminary evidence that an offspring polygenic risk score for major depressive disorder (PRS-MDD), based on European ancestry, interacts with prenatal maternal depressive symptoms (GxE) on neonatal right amygdalar (US and Asian cohort) and hippocampal volumes (Asian cohort). However, to date, this GxE interplay has only been addressed by one study and is yet unknown for a European ancestry sample. We investigated in 105 Finnish mother-infant dyads (44 female, 11-54 days old) how offspring PRS-MDD interacts with prenatal maternal depressive symptoms (Edinburgh Postnatal Depression Scale, gestational weeks 14, 24, 34) on infant amygdalar and hippocampal volumes. We found a GxE effect on right amygdalar volumes, significant in the main analysis, but nonsignificant after multiple comparison correction and some of the control analyses, whose direction paralleled the US cohort findings. Additional exploratory analyses suggested a sex-specific GxE effect on right hippocampal volumes. Our study is the first to provide support, though statistically weak, for an interplay of offspring PRS-MDD and prenatal maternal depressive symptoms on infant limbic brain volumes in a cohort matched to the PRS-MDD discovery sample.